Methodological crisis in the social and human sciences and ways to overcome the crisis - Berkov, Vladimir F. (Journal of the Belarusian State University. Sociology, 2019)
The article shows that at the turn of XX–XXI centuries social and human sciences are found to be in a serious methodological crisis. Under pressure from society with corresponding ideological influence the materialist conception of history was put to the question and replaced by the different variations of exploded positivism. Overcoming the crisis is associated with a return to the dialectics in its Marxist, activity-practical sense (using such categories as «need», «interest», «value», «goal», «mean», «result» etc.).